Perovskite Nanocrystals: Synthesis, Stability, and Optoelectronic Applications. Issue 3 (7th February 2021) - Wang, Shizhe; Yousefi Amin, Amir Abbas; Wu, Linzhong; Cao, Muhan; Zhang, Qiao; Ameri, Tayebeh
Abstract : Metal halide perovskite (MHP) materials, named as the game changers, have attracted researchers' attention worldwide for over a decade. Among them, nanometer‐scale perovskite nanocrystals (PNCs) have exhibited attractive photophysical properties, such as tunable bandgaps, narrow emission, strong light‐absorption coefficients, and high defect tolerance, because they combined the excellent optoelectronic properties of bulk perovskite materials with strong quantum confinement effects of the nanoscale. These materials possess a great potential to be applied in the optoelectronic devices. For commercial applications in devices like solar cells (SCs), light‐emitting diodes (LEDs), and photodetectors (PDs), the stability of PNCs against ambient atmosphere like oxygen and moisture, as well as light and high temperature is crucial. Herein, the synthetic methods and stability issues of the PNCs are introduced first, followed by the introduction of the strategies for improving their stability by encapsulation. The applications of PNCs in various optoelectronic devices are then briefly presented. Finally, the remained challenges in improving the stability of PNCs toward the PNC‐based optoelectronics with high performance and great durability are addressed. Abstract : Herein, the synthetic methods and stability issues of perovskite nanocrystals (PNCs) are first summarized, followed by introducing different strategies of encapsulation to improve their stability. The applications of PNCs in various optoelectronic devices are then briefly presented. Finally, the remaining challenges in improving the stability of PNCs toward the PNC‐based optoelectronics with high performance and great durability are addressed.